2011
DOI: 10.1111/j.1365-2125.2011.04054.x
|View full text |Cite
|
Sign up to set email alerts
|

High dose methotrexate chemotherapy: pharmacokinetics, folate and toxicity in osteosarcoma patients

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• High dose methotrexate (HD MTX) is generally well tolerated, although unpredictable acute toxicities occur frequently.• Low overall toxicity in paediatric patients and increased liver toxicity in adults has been reported, but there are no reports addressing the relationship between acute liver toxicity and gender in patients treated with HD MTX. • Previous studies in animals suggested involvement of the 7-hydroxy-methotrexate metabolite in acute liver toxicity, but thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 31 publications
4
83
2
3
Order By: Relevance
“…11,12,[20][21][22][38][39][40] In this study, gastrointestinal toxicity in the form of vomiting (70%) was commonly found.…”
Section: Resultsmentioning
confidence: 99%
“…11,12,[20][21][22][38][39][40] In this study, gastrointestinal toxicity in the form of vomiting (70%) was commonly found.…”
Section: Resultsmentioning
confidence: 99%
“…About 1.8% of patients develop acute renal failure 5 , the leading cause of death related to hdmtx chemotherapy. Because of those complications, therapy with hdmtx properly requires rigorous pharmacokinetic monitoring and rescue with leucovorin [7][8][9] . Moreover, the expertise and technology required for proper hdmtx administration is unavailable in many hospitals, particularly in China.…”
Section: Introductionmentioning
confidence: 99%
“…It also presents high PK variability, in particular its drug clearance, which ranges from 40 to 400 mL/min [69]. Moreover, methotrexate PK variability has been linked to both efficacy and toxicity, including myelosuppression, hepatotoxicity, and renal toxicity [70]. Typical doses of weekly methotrexate range from 30 to 50 mg/m 2 ; however, doses >1 g/m 2 may help to overcome resistance mechanisms of cancer cells, promote the formation of active metabolites, and increase drug penetration into the cerebral spinal fluid.…”
Section: Methotrexatementioning
confidence: 99%